2011
DOI: 10.2166/wh.2011.156
|View full text |Cite
|
Sign up to set email alerts
|

New USEPA water quality criteria by 2012: GOMA concerns and recommendations

Abstract: The Gulf of Mexico Alliance (GOMA) was tasked by the five Gulf State Governors to identify major issues affecting the Gulf of Mexico (GoM) and to set priorities for ameliorating these problems. One priority identified by GOMA is the need to improve detection methods for water quality indicators, pathogens and microbial source tracking. The United States Environmental Protection Agency (USEPA) is tasked with revising water quality criteria by 2012; however, the locations traditionally studied by the USEPA are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The Annapolis Protocol first identified the value of a comprehensive sanitary inspection of recreational waters to identify all sources of potential pathogens, a concept further developed over the past decade (Boehm et al, 2009a;Gooch-Moore et al, 2011;Abdelzaher et al, 2013). The Annapolis Protocol introduced the concept of a risk-based approach, and acknowledged that common FIO standards across all waters did not account for the unequal probability of pathogen presence in faecal contamination from different sources.…”
Section: O V E R V I E W O F ' C a L L -T O -A C T I O N ' D O C U M mentioning
confidence: 99%
See 1 more Smart Citation
“…The Annapolis Protocol first identified the value of a comprehensive sanitary inspection of recreational waters to identify all sources of potential pathogens, a concept further developed over the past decade (Boehm et al, 2009a;Gooch-Moore et al, 2011;Abdelzaher et al, 2013). The Annapolis Protocol introduced the concept of a risk-based approach, and acknowledged that common FIO standards across all waters did not account for the unequal probability of pathogen presence in faecal contamination from different sources.…”
Section: O V E R V I E W O F ' C a L L -T O -A C T I O N ' D O C U M mentioning
confidence: 99%
“…The sole reliance on FIO levels in water as a mechanism for classifying recreational waters was challenged by the Annapolis Protocol, a document prepared for the World Health Organization and authored by many of the acknowledged world experts in the field (WHO, 1999), well over a decade ago. The Annapolis Protocol first identified the value of a comprehensive sanitary inspection of recreational waters to identify all sources of potential pathogens, a concept further developed over the past decade (Boehm et al ., 2009a; Gooch-Moore et al ., 2011; Abdelzaher et al ., 2013). The Annapolis Protocol introduced the concept of a risk-based approach, and acknowledged that common FIO standards across all waters did not account for the unequal probability of pathogen presence in faecal contamination from different sources.…”
Section: Overview Of ‘Call-to-action’ Documentsmentioning
confidence: 99%
“…Since 60%–80% of the impaired waters in the US, are due to non-point sources of FIB [ 23 , 24 , 25 ], these results indicate that the health effects predicted by the 2012 RWQC will not be applicable to the majority of the recreational water sites in the US. In this regard, Gooch-Moore et al [ 26 ] reported their concern that the 2012 RWQC may not be applicable to beaches in the Gulf of Mexico, where non-point sources of FIB and environmental conditions differ from those beaches that were selected for the development of the 2012 RWQC.…”
Section: Theory Assumptions and Interpretation Of 2012 Rwqcmentioning
confidence: 99%
“…The USA has begun to utilize qPCR methods at some recreational beaches on a voluntary basis. This was prompted by a lawsuit against the US Environmental Protection Agency (EPA) filed by the Natural Resources Defence Council (NRDC) and others which argued that USEPA had not delivered on its intention to explore new or revised water-quality criteria linked to rapid test methods (Gooch-Moore et al 2011 ). In response, the USEPA published the 2012 revised Recreational Water Quality Criteria (RWQC) for FIOs in marine and fresh waters (U.S. EPA 2012 ); within these criteria there are regulatory action thresholds for enterococci as determined by qPCR.…”
Section: Introductionmentioning
confidence: 99%